False negative β‐2 transferrin in the diagnosis of cerebrospinal fluid leak in the presence of Streptococcus pneumoniae. (29th September 2014) - Korem, Maya; Ovadia, Haim; Paldor, Iddo; Moses, Allon E.; Block, Colin; Eliashar, Ron; Hirshoren, Nir
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The objectives of this study were to examine the presence of β‐2 transferrin (β2TRNSF) in cerebrospinal fluid (CSF) contaminated in vitro by various bacteria and explore the mechanism (passive or active) responsible for β2TRNSF elimination. Early diagnosis of CSF leakage may change treatment decisions and minimize the risk of meningitis and encephalitis. β2TRNSF is a protein present exclusively in CSF. Its detection is highly useful in cases of CSF leakage, although it has never been examined in the presence of central nervous system infection. Study Design Prospective patient analysis. Methods Sterile CSF drawn from patients was contaminated in vitro with several microorganisms chosen for their ability to cause neurosurgical‐related infections: Streptococcus pneumoniae, methicillin‐sensitive Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa. β2TRNSF was examined at two time points: following immediate inoculation (t0) and following an overnight incubation (t18) over various bacterial concentrations. Samples of CSF inoculated with S pneumoniae were also examined in the presence of ciprofloxacin. For β2TRNSF analysis we used immunoblotting electrophoresis and enzyme‐linked immunosorbent assay (ELISA). Results CSF samples collected from nine patients were analyzed. β2TRNSF was not detected following S pneumoniae inoculation at both time points when immunoblotting electrophoresis was used. Quantitative analysis using ELISA demonstrated significant β2TRNSF concentration decrease. The addition of ciprofloxacin led to the same results. Conclusions CSF leak detection using β2TRNSF may be deceiving in the presence of a S pneumoniae cerebral nervous system infection. A passive process is suggested, as β2TRNSF disappeared either immediately or following incubation with inactive bacteria. Level of Evidence NA Laryngoscope, 125:556–560, 2015